2008
DOI: 10.1088/1367-2630/10/8/083016
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot as thermal rectifier

Abstract: We report the observation of thermal rectification in a semiconductor quantum dot, as inferred from the asymmetric line shape of the thermopower oscillations. The asymmetry is observed at high in-plane magnetic fields and caused by the presence of a high orbital momentum state in the dot.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 22 publications
3
168
0
1
Order By: Relevance
“…Theoretical models for thermal rectifiers are proposed relying on various mechanisms (Roberts and Walker, 2011), including different temperature-dependent thermal properties between dissimilar materials at a contact (Stevenson et al, 1991;Dames, 2009;Kobayashi et al, 2009), asymmetric design of nanostructure (Wu and Li, 2008;Yang et al, 2009), and quantum thermal systems, such as quantum dots and other quantum heterojunctions (Scheibner et al, 2007;Ruokola et al, 2009;Wu and Segal, 2009;Ren and Zhu, 2013a). Similar concepts are even extended to the spin Seebeck diode and transistor (Ren, 2013;Ren and Zhu, 2013b;Ren et al, 2013), and the multiferroic thermal diode (Chotorlishvili et al, 2015), multiferroic switch and memory .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models for thermal rectifiers are proposed relying on various mechanisms (Roberts and Walker, 2011), including different temperature-dependent thermal properties between dissimilar materials at a contact (Stevenson et al, 1991;Dames, 2009;Kobayashi et al, 2009), asymmetric design of nanostructure (Wu and Li, 2008;Yang et al, 2009), and quantum thermal systems, such as quantum dots and other quantum heterojunctions (Scheibner et al, 2007;Ruokola et al, 2009;Wu and Segal, 2009;Ren and Zhu, 2013a). Similar concepts are even extended to the spin Seebeck diode and transistor (Ren, 2013;Ren and Zhu, 2013b;Ren et al, 2013), and the multiferroic thermal diode (Chotorlishvili et al, 2015), multiferroic switch and memory .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 an experimental study by Scheibner et al showed thermally rectifying behavior in quantum dots when high in-plane magnetic fields are present as a result of the presence of a high orbital momentum state in the dot [93]. Their analysis showed a stronger coupling to the drain than the source when not in the ground state.…”
Section: Quantum Thermal Systemsmentioning
confidence: 99%
“…For example, if one could use phononic devices to control, direct, and utilize the heat generated in electronic circuits to add processing power, one would achieve an improvement over the present situation, where we face the major problem of removing the heat from the circuit, only to send it to waste. Directional thermal effects were first observed many years ago, but the past decade has seen several advances in the field of phononics, with models for thermal diodes [221,222] and experimental realizations of micro/nanoscopic solid-state thermal rectifiers [223,224]. Researchers have also proposed thermal transistors, gates, and memory [225][226][227].…”
Section: Beyond Electron Sources: What Else Do We Learn From Carbon Nmentioning
confidence: 99%